Phimophis guerini (Duméril, Bibron and Dumeril, 1854) (Serpentes: Dipsadidae): distribution extension in Paraiba, Brazil - Gentil Filho; Gindomar Santana; Washington Vieira; Rômulo Alves; Paulo Montenegro; Marco Freitas (Check List, 2012)
We provide a new record of Phimophis guerini from the Atlantic Forest in Paraiba state and a review of the distribution of the species.